Success With BEC Higher. Students Book. - Dummett, P., Benn, C. (Oxford Summertown Publishing, 2009)
BEC(Business English Certificates) is an internationally recognised business qualification which demonstrates an ability to use English in professional contexts. As a University of Cambridge ESOL examination, it is used as a suitable entry requirement by academic institutions and for recruitmrnt by international companies.
Keywords: English Practice